Antiplatelet Therapy In Ckd (Journal of Chittagong Medical College Teachers' Association, 2013)
Chronic kidney disease (CKD) patients are at increased risk of cardiovascular events (CVE) than general population. Antiplatelet agents (APA) reduce CVE in patients with normal kidney function. Whether they are of same efficacy and safety in CKD population is questionable because most of the studies did not include CKD population in their trial of APAs. At one hand there is poor response to APAs because of altered metabolism, on the other hand there is paradoxical more risk of major bleeding. This review will, address these issues of APAs use in CKD.JCMCTA 2013; 24 (1):70-75